-2x+6y=6

-7x+8y=-5

2 answers

multiply the top by positive 8 and multiply the bottom by negative 6. then cancel out the y's and solve for x. plug x back into anyone and solve for y.
hmm. sounds like elimination to me.

For substitution, pick either equation and solve for x (or y):

-2x+6y=6
6y = 2x+6
y = x/3 + 1

Now substitute that into the other equation:

-7x+8y = -5
-7x + 8(x/3 + 1) = -5
-7x + 8x/3 + 8 = -5
-13x/3 = -13
x = 3
so, y = x/3+1 = 2

be sure to plug (3,2) into the original equations to make sure you (or I!) didn't make a mistake.